Cardiorespiratory health effects of particulate ambient air pollution exposure in low-income and middle-income countries: a systematic review and meta-analysis - Newell, K; Kartsonaki, C; Lam, K; Kurmi, O (Elsevier, 2017)
Background The majority of prospective studies on the health effects of particulate ambient air pollution (AAP) exposure have focused on high income countries where pollutant concentrations are much lower than in low and/or middle income countries (LMICs) and sources of pollution different. This systematic review and meta-analysis examines the cardiorespiratory health impacts of particulate AAP exposure in LMICs exclusively. Methods Systematic searching located studies examining cardiorespiratory health impacts of particulate AAP exposure in LMICs. Estimates were pooled by pollutant type (PM2.5, PM10), lag and outcome, and presented as excess relative risk per 10µg/m3 increase in particulate AAP. Publication bias and sources of heterogeneity were explored and sub-group analysis performed pooling estimates by specific outcomes, region, and city. The study protocol is registered with PROSPERO number CRD42016051733. Findings From 1553 abstracts, 91 met the inclusion criteria. Only four long-term exposure studies from China were identified and not included in the meta-analysis. A 10µg/m3 increase in same-day PM2.5 was associated with a 0·47% (95% CI 0·34, 0·61) and 0·57% (0·28, 0·86) increase in cardiovascular and respiratory mortality respectively. Risk of respiratory morbidity was greatest at 2 day moving average lags, with a pooled increase of 0·33% (0·07, 0·6) and 0.76% (0·52, 1·01) for 10µg/m3 increases in PM10 and PM2.5 concentrations respectively. Stronger associations were found for mortality and morbidity in Latin America and the Caribbean versus East Asia and Pacific, however heterogeneity for these findings was high. Interpretation Short term exposure to particulate AAP is associated with increases in morbidity and mortality in LMIC’s with regional-specific variations apparent.